2018
DOI: 10.1002/ldr.2974
|View full text |Cite
|
Sign up to set email alerts
|

High Arctic coasts at risk—the case study of coastal zone development and degradation associated with climate changes and multidirectional human impacts in Longyearbyen (Adventfjorden, Svalbard)

Abstract: Longyearbyen is the major administrative, touristic, and scientific centre in Svalbard and so‐called ‘European Gateway’ to the Arctic. The number of inhabitants and tourists as well as community infrastructure has significantly expanded over the recent decade, and present‐day community faces development thresholds associated with climate warming and disturbance of cold region landscape. Coastal zone is a key interface where severe environmental changes impact directly on Longyearbyen infrastructure. We applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 45 publications
1
31
0
Order By: Relevance
“…The highest erosion rate in the Arctic was registered on Alaskan coast (Drew Point) with a value of −8.4 m/year, while the lowest erosion rate was reported in Svalbard. Other reported erosion rates in Svalbard range from −0.5 to −4.5 m/year for Longyearbyen [21], −0.26 m/year for Isbjørnhamna [48], −0.34 m/year and −0.47 m/year for ice-poor cliffs and ice-rich cliffs, respectively [32]. With a value of EPR of −0.21 m/year, our study area can be framed in around the average erosion rate previously reported in Svalbard.…”
Section: Shoreline Displacementmentioning
confidence: 99%
See 3 more Smart Citations
“…The highest erosion rate in the Arctic was registered on Alaskan coast (Drew Point) with a value of −8.4 m/year, while the lowest erosion rate was reported in Svalbard. Other reported erosion rates in Svalbard range from −0.5 to −4.5 m/year for Longyearbyen [21], −0.26 m/year for Isbjørnhamna [48], −0.34 m/year and −0.47 m/year for ice-poor cliffs and ice-rich cliffs, respectively [32]. With a value of EPR of −0.21 m/year, our study area can be framed in around the average erosion rate previously reported in Svalbard.…”
Section: Shoreline Displacementmentioning
confidence: 99%
“…This position gives a complex climatic situation where different oceanic currents influence both long-term climate and short-term meteorology of the islands. The focus of this study is the shoreline of Hiorthhamn-on the northeastern shore of Adventfjorden (Figure 2b), approximately 3 km north of Longyearbyen (Figure 2c), which is the major administrative, tourist and scientific centre in Svalbard, also named "European Gateway" to the Arctic [21]. The Hiorthhamn fjord side is step-shaped with south-west-oriented slopes running down from the top of the Hiorthfjellet mountain to the Advent fjord shore.…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…zones (Crowell, Douglas, & Leatherman, 1997;Jaskólski, Pawłowski, & Strzelecki, 2018;Mukhopadhyay et al, 2012;Scavia et al, 2002). The important techniques used to study the periodic changes in shorelines include physical surveys; satellite imageries; aerial photography (Duru, 2017;Ford, 2013); and numerical modeling methods (Noujas, Thomas, & Badarees, 2016;Pereira et al, 2013).…”
mentioning
confidence: 99%